Masquereading Léon Damas' Mine de riens - Gyssels, Kathleen (Dalhousie French Studies, 2020)
In French Guiana, “macoumé” is the offensive term for the supposedly or proven homosexual. In a long passage from Black-Label, the poet rhymed, in a self-portrait as the “Beautiful Choir Child”, the roses “miraculées, immaculées, immatriculées” (BL 38). I have always heard the term put in quotation marks: “macoumé.” Starting from the concepts of “Masquereading” (Marie-Hélène Bourcier) and “homotextuality” (Jean-Pierre Rocchi), I propose a new approach to this impudent and immoralist (Gide launched Damas, after all) poetry. He will have been a “maskilili”, a Native American devil who is never where he is expected to be, defying expectations and above all putting his right shoe on his left foot.